Gifted education and talent development for all - Renzulli, Joseph S. (2008)
Traditional methods of schooling can fail to bring about schools as places for developing the broadest and richest experiences for creating talent in the young. The field of gifted education has put forward many innovations that have become mainstays of the American educational system. The Schoolwide Enrichment Model comprises strategies for increasing student effort, enjoyment, and performance, and for integrating a range of advanced-level learning experiences and thinking skills into all curricular areas. Every school has students within it who possess the highest potential for advanced-level learning, creative problem solving, and the motivation to pursue rigorous and rewarding work. Rather than being sources for the acquisition of information, schools should be places for developing the talents of all students.